2011
DOI: 10.5897/jeif11.126
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of foreign aid in sub-Saharan Africa: Does disaggregating aid into bilateral and multilateral components make a difference?

Abstract: Inspired by the contradicting findings of studies on aid effectiveness and the recently emerging dissatisfaction of scholars with the methodologies of earlier works, this study took up the examination of the effectiveness of bilateral and multilateral aids on economic growth. To this end, the study applied the estimation technique of system-GMM (system-generalized method of moments) to panel data of 42 Sub-Saharan African countries collected from secondary sources for the years 1980 through 2007. For the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…This indicates a substantial improvement even though the trajectory remained on the negative trend but with less severity in the long run. This outcome supports the findings in Wako (2011) and Cordella and Ulku (2007) which suggest that bilateral aid and degree of concessionality have not been effective in promoting growth in the SSA. In contrast, our estimation based on concessional debts from multilateral sources revealed that multilateral concessional aids had a positive impact on growth both in the short run and long run.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This indicates a substantial improvement even though the trajectory remained on the negative trend but with less severity in the long run. This outcome supports the findings in Wako (2011) and Cordella and Ulku (2007) which suggest that bilateral aid and degree of concessionality have not been effective in promoting growth in the SSA. In contrast, our estimation based on concessional debts from multilateral sources revealed that multilateral concessional aids had a positive impact on growth both in the short run and long run.…”
Section: Discussionsupporting
confidence: 85%
“…Economic growth in developing countries is believed to have been negatively influenced by the uncertainty associated with the flows of ODA and aid in most investigated cases (Stojanov et al, 2019). Wako (2011), for instance, examined the effect of bilateral and multilateral aid on economic growth in the SSA region using the system generalized method of moments (GMM) estimator. The findings showed that multilateral and bilateral aids were ineffective at enhancing economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Similarly, Karras (2006), Clemens, Radelet, andBhavnani (2004) and Ardnt et al (2010) found a positive and statistically significant relation between aid and growth. In contrast, Wako (2011) had a different perspective and argued that multilateral and bilateral aids are ineffective at enhancing growth. In a related study, Ogundipe et al (2014) are of the view that aid has no significant influence on real GDP per capita in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Or, as Gillanders (2016) reveals, whilst direct aid seems to work in terms of generating economic growth, it does not do so to a level that can be called transformative. Relatedly, Wako (2011) concludes that bilateral and multilateral aid on its own, or in interaction with policy, is ineffective at enhancing economic growth.…”
Section: Interventions In Africa: How the Past Informs The Presentmentioning
confidence: 99%